A safety and feasibility trial of 131I‐MIBG in newly diagnosed high‐risk neuroblastoma: A Children's Oncology Group study. Issue 10 (24th May 2021) - Weiss, Brian D.; Yanik, Gregory; Naranjo, Arlene; Zhang, Fan F.; Fitzgerald, Wendy; Shulkin, Barry L.; Parisi, Marguerite T.; Russell, Heidi; Grupp, Stephan; Pater, Luke; Mattei, Peter; Mosse, Yael; et al.
Abstract: Introduction: 131 I‐meta‐iodobenzylguanidine ( 131 I‐MIBG) is effective in relapsed neuroblastoma. The Children's Oncology Group (COG) conducted a pilot study (NCT01175356) to assess tolerability and feasibility of induction chemotherapy followed by 131 I − MIBG therapy and myeloablative busulfan/melphalan (Bu/Mel) in patients with newly diagnosed high‐risk neuroblastoma. Methods: Patients with MIBG‐avid high‐risk neuroblastoma were eligible. After the first two patients to receive protocol therapy developed severe sinusoidal obstruction syndrome (SOS), the trial was re‐designed to include an 131 I‐MIBG dose escalation (12, 15, and 18 mCi/kg), with a required 10‐week gap before Bu/Mel administration. Patients who completed induction chemotherapy were evaluable for assessment of 131 I‐MIBG feasibility; those who completed 131 I‐MIBG therapy were evaluable for assessment of 131 I‐MIBG + Bu/Mel feasibility. Results: Fifty‐nine of 68 patients (86.8%) who completed induction chemotherapy received 131 I‐MIBG. Thirty‐seven of 45 patients (82.2%) evaluable for 131 I‐MIBG + Bu/Mel received this combination. Among those who received 131 I‐MIBG after revision of the study design, one patient per dose level developed severe SOS. Rates of moderate to severe SOS at 12, 15, and 18 mCi/kg were 33.3%, 23.5%, and 25.0%, respectively. There was one toxic death. The 131 I‐MIBG and 131 I‐MIBG+Bu/Mel feasibility rates at the 15 mCi/kg dose level designated for further study were 96.7% (95% CI: 83.3%‐99.4%) and 81.0% (95% CI: 60.0%‐92.3%). Conclusion: This pilot trial demonstrated feasibility and tolerability of administering 131 I‐MIBG followed by myeloablative therapy with Bu/Mel to newly diagnosed children with high‐risk neuroblastoma in a cooperative group setting, laying the groundwork for a cooperative randomized trial (NCT03126916) testing the addition of 131 I‐MIBG during induction therapy.